Associations between alcohol and cannabis use before and during the COVID-19 pandemic: Results of a community survey. (December 2022) - Goodyear, Kimberly; Moyo, Patience; Avila, Jaqueline C.; Ahluwalia, Jasjit S.; Monnig, Mollie A.
Highlights: Overall alcohol use and cannabis use decreased from before and during the pandemic. Overall there was a decrease in the proportion of individuals who used substances. Home delivery was associated with higher alcohol and cannabis use. Abstract: The COVID-19 pandemic has impacted individuals around the world, creating unprecedented challenges. Due to lockdowns and social distancing measures, many people have turned to contactless modes of obtaining alcohol and other substances (e.g., home delivery). This study investigated associations between alcohol and cannabis use before and during the initial months of the COVID-19 pandemic and factors associated with use. An online, cross-sectional survey with a non-probability sample ( N = 1126) was conducted in Northeast states during June-July 2020. Outcomes examined prevalence of alcohol and cannabis use for the overall sample and predictors of use in individuals who used substances. In the overall sample, we found that alcohol and cannabis use decreased from before to during the pandemic. For individuals who drank alcohol, higher pre-pandemic drinking, mid-range household income, and obtaining alcohol through home delivery were associated with higher alcohol drinking during the pandemic. For individuals who used cannabis, higher pre-pandemic cannabis use and obtaining cannabis through home delivery were associated with higher cannabis use during the pandemic. Overall, from before to during the pandemic, we found a decrease in the proportion of individuals who used substances and no changes in quantity for individuals who continued to use substances. Home delivery was associated with greater use of alcohol and marijuana, supporting a need for further research on risk factors for heavier substance use.